Technical demands across playing positions of the Asian Cup in male football. (4th July 2019) - Ermidis, Georgios; Randers, Morten B.; Krustrup, Peter; Mohr, Magni
ABSTRACT: The aim of this study was to compare technical variables by playing positions in football during the 2015 Asian Cup. Top-level male football players (n = 202) that completed the full 90-min game were considered. Match-analysis data were collected using OPTA Sportsdata (www.optasports.com ). Kruskal–Wallis H non-parametric test revealed that external midfielders (EM) scored more goals than fullbacks (FB) (p = 0.042), and that FB had less attempts (to score a goal) than central midfielders (CM), EM and forwards (FW), whereas central defenders (CD) had less attempts than FW (p < 0.05). CM performed more passes than CD, EM and FW, while FW performed less passes than CD, FB and CM. CD and CM performed more successful passes than FB and FW (p < 0.05), and CM also had more passes than EM (p < 0.05). Moreover, FW had more aerial duels (50–50 contests) than CM, FB and EM (p < 0.05). Similar numbers of aerial duels occurred for CD and FW. Ground duels occurred less (p < 0.05) frequently for CD compared to FB, CM, EM and FW. In conclusion, differences in technical events were observed between the various playing positions during competitive elite football matches, making it valuable considering the technical demands of players during group training as well as individualised training.